Peace treaty from Georg of Podiebrady - Magda Schusterová (Journal on European History of Law, 2011)
The preambles are generally considered to constitute an introductory or even poetical part of a legal text. The promulgation of the document is announced in the preamble and the reason for its promulgation. However a closer examination reveals that their content could be far reaching. Namely the preamble of the peace treaty of the Bohemian King George of Podĕbrady (1458-1471) reflects interesting philological and juridical aspects of the medieval times, in that it mentions the general peace mission of the princes and their natural commitment to defend the Christian faith. We also find therein citations from the Holy Bible, from the Codex Iustinianus or a partially copied imperial writing of Frederick III. However the Bohemian text does not go beyond the tradition of the late medieval preambles in form and content- peace making among European princes in order to fight enemies of Christianity was one of the common topos at this time.